Determination of Management Decision Quality: Integration, Effectiveness, Development of Management Information Systems - Sri Wulandari; Hapzi Ali (Dinasti International Journal of Management Science, 2023)
The Influence of Integration, Effectiveness and Development on the Quality of Management Decisions is a scientific article in a literature study that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Executive Support Systems For Business. The method of writing this article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this article are that: 1) Integration has an effect on the Quality of Management Decisions; 2) Effectiveness influences the Quality of Management Decisions; and 3) Development influences the Quality of Management Decisions.